Design guide for steel at elevated temperatures and high strain rates (FABIG technical note ;, 2001)
'High strength steel is often used on offshore structures where there is a risk of accidental fire and blast loads. Design for fire requires knowledge of elevated temperature data while design for blast loads requires knowledge of high strain rate material data. This document provides guidance on elevated temperature and high strain rate material property data that is currently available for high strength steels used specifically for offshore structures. The guidance covers the data required to carry out both simplified design checks and advanced nonlinear analyses."--Knovel.